2016
DOI: 10.21448/http-ijate-net-index-php-ijsm.243308
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and insecticidal activity of volatile compounds of three algae species of Oman Sea

Abstract: Many of the volatile oils showed important biological and pharmacological activities, these compounds as part of the traditional medicine in many cultures used as long time. Potencies of them caused these natural products gained many scientific researches in felid of natural products. The volatile oils of Actinotrichia fragilis (Forsskål) Børgesen, Liagora ceranoides J.V.Lamouroux and Colpomenia sinuosa (Mertens ex Roth) Derbes and. Solier were extracted by hydrodistillation. These volatile oils were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…Antibacterial activity of C. intricatum extract in opposition to S. aureus and MRSA is similar to that reported from methanol extracts of Codium species (C. tomentosum, C. tomentosum, C. dichotomum and C. fragile), where high inhibitory activity was noted [45]. Pasdaran et al [10] reported the antibacterial activity of A. fragilis volatile oil against Pseudomonas aeruginosa, E. coli and Staphylococcus aureus. Salem et al [49] reported the antibacterial activity of A. fragilis extracts against E. coli, S. aureus, E. feacalis, Salmonella sp., B. cereus and P. aeruginosa.…”
Section: Antibacterial Activity and Mic Determinationsupporting
confidence: 76%
See 1 more Smart Citation
“…Antibacterial activity of C. intricatum extract in opposition to S. aureus and MRSA is similar to that reported from methanol extracts of Codium species (C. tomentosum, C. tomentosum, C. dichotomum and C. fragile), where high inhibitory activity was noted [45]. Pasdaran et al [10] reported the antibacterial activity of A. fragilis volatile oil against Pseudomonas aeruginosa, E. coli and Staphylococcus aureus. Salem et al [49] reported the antibacterial activity of A. fragilis extracts against E. coli, S. aureus, E. feacalis, Salmonella sp., B. cereus and P. aeruginosa.…”
Section: Antibacterial Activity and Mic Determinationsupporting
confidence: 76%
“…Recently, due to the resistance of different pathogenic bacteria and pests to antibiotics and insecticidal agents, finding new active components against these health and environmental problems is one of the major areas of medical and agricultural research. The peculiarity of the marine environment and the high biological activity of marine natural products make algal metabolites a fascinating source for finding new antimicrobial and insecticidal compound [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The volatile oils from Actinotrichia fragilis, Liagora ceranoides, and Colpomenia sinuosa were hydrodistilled and contained different aliphatic alcohols and long-chain hydrocarbons as the major components. They caused 55-90% and 60-80% mortality to pests of stored products Oryzaephilus mercator and Tribolium castaneum, respectively, at a dose of 12 µL/L air after 48 h of fumigation exposure [119].…”
Section: Dermatophagoides Pteronyssinusmentioning
confidence: 99%
“…The volatile oils of A. fragilis caused 80-90% mortality in both T. castaneum and O. mercator and consisted of 49% aliphatic alcohols, mainly 1-dodecanol (39.6%) [119]. The insecticidal activity of 1-dodecanol was suggested to be related to the developing cuticle, producing a disruption in the cuticular tanning process [120].…”
Section: Dermatophagoides Pteronyssinusmentioning
confidence: 99%